Tidal Characteristics in the Northern Coast of Central Java (a Case Study in Semarang, Indonesia) - Prayogo, Luhur Moekti; Yuliardi, Amir Yarkhasy; Spanton, Perdana Ixbal (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2024)
Tides are a phenomenon that affects the dynamics of coastal waters. This study aims to analyze the characteristics of tides on the North Coast of Semarang, Central Java using the Least Square method. The tidal data used is in September 2020 from the Geospatial Information Agency open source data. The results showed that the tidal pattern in this area is dominated by a semi-diurnal component with a Formzahl number of 1.44, which means that the tidal type is mixed tending to be semi-diurnal. The main component identified is M2 (0.4 meters), which is the main semi-diurnal component influenced by the gravitational force of the moon. In addition, the S2 component (0.3 meters), which is a semi-diurnal component influenced by the gravitational force of the sun. In addition, the influence of extreme weather such as storms causes an increase in tide height, which triggers tidal flooding and coastal abrasion. The study concludes that an understanding of tidal characteristics is essential for sustainable coastal management. The results of this analysis can be used as a basis for mitigating environmental impacts, such as abrasion and tidal flooding, as well as for optimizing the economic activities of tide-dependent coastal communities, such as fisheries and ponds.